Skin Aging and Basic Skin Care in Elderly - Damayanti Damayanti (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: In the last few decades, the world population of older adults is increasing significantly. One-fifth of the global population will be more than 65 years old by the year 2050. Of interest is those 85 years old and older has the fastest growing segmen of population. Since the human population is living longer, chronic disease including skin disease and skin aging problems, will be more prevalence. Purpose: To review the pathogenesis and clinical manifestation of skin aging, and to review basic skin care in elderly. Reviews: Skin aging is caused by endogen and extrinsic factors. Skin aging divided into intrinsic (chronologic) skin aging and extrinsic photoaging. The elderly population, that has rapidly increase, needs for basic skin care in order to delay skin aging process.  Basic skin care consist of cleansing, hidrating, replenishing, and protection. Photoprotection, such as avoiding midday sun, using photoprotective clothes, hat, sunglasses, and administration of sunscreen, has important role in preventing skin damage. Conclusion: Good visible aging process can be delayed by preventive skin care to reach successful aging, which has good physical health, good mental health and adaptive psychosocial functioning, so that older person can live a happy, health and  active life.